Motor expertise affects the unconscious processing of geometric forms - Geng,Jiaxian; Meng,Fanying; Wang,Chao; Haponenko,Hanna; Li,Anmin (PeerJ, 2020)
Background The unconscious processing of information is an important skill used by competitive athletes to handle the rapidly changing movements of opponents and equipment. Previous studies have shown that unconscious information processing among athletes is better than that among non-athletes in the sports-specific domain. However, it is not yet clear whether athletes also show superior unconscious information processing in the general cognitive domain. Methods Twenty-five competitive table tennis players (athletes) and 26 aged-matched non-athletic college students (non-athlete controls) were recruited for this study. Participants first performed a masked priming task that used geometric shapes as primes and targets to examine unconscious information processing in the general cognitive domain. As a control, participants then completed a prime identification task to determine whether they could consciously detect the priming geometric forms. Reaction times and error rates were analyzed to examine whether motor expertise influenced unconscious information processing in the general domain. Nineteen athletes and 17 non-athletes from our present study, which used general stimuli, also participated in our previous study, which used sport-specific stimuli. The strength of the unconscious response priming effect was analyzed to examine whether the effect of motor expertise on unconscious processing could be transferred from a sports-specific domain to a general domain. Results Signal detection analyses indicated that neither athletes nor non-athletes could consciously perceive the priming stimuli. Two-way repeated-measures analyses of variance followed by simple main effects analyses of the masked priming performance, indicating that athletes responded faster and committed fewer errors when the priming stimulus was congruent with the target stimulus. These results suggested that athletes exhibited a significant unconscious response priming effect of geometric forms. By contrast, non-athletes did not respond faster or commit fewer errors for congruent vs. incongruent conditions. No significant difference was detected between athletes and non-athletes in error rates for congruent trials, but athletes committed significantly more errors than non-athletes on incongruent trials. The strength of the unconscious response priming effect that athletes exhibited was greater than that for non-athletes, both in the present study with general stimuli and in our previous study with sport-specific stimuli. Conclusion The results indicated that motor expertise facilitated the unconscious processing of geometric forms, suggesting that the influence of motor expertise on unconscious information processing occurs not only for the sports-specific domain but also transfers to the general cognitive domain.
Keywords: Motor expertise; Unconscious processing; Geometric forms; Table tennis players